Eating attitudes and risk of eating disorders in adolescents: role of the thinness stereotype - Cardoso, Susana (2014)
Introduction: In societies where thinness is seen as a sign of ideal beauty, there is a significant social pressure for teenagers to follow this model. Such cultural stereotypes can create risky situations in what eating behaviors are concerned. Those risky situations are associated with attitudes connected with fear of gaining weight and with low self-esteem. Objective: To identify risky eating attitudes in adolescents and to characterize associations between eating attitudes (promoting risk of developing an eating disorder), sex and age. Methods: 358 adolescents (convenience sample) of two secondary schools (aged 14-18 years) were asked to complete the EAT-25 (eating attitudes test) (range from 0 to 75; cutoff=19). Results: We found 4, 5% of increased-risk cases (boys: scores between 20 and 25; girls: scores between 19 and 35). No statistically significant differences were found between overall score of EAT-25 and age. Girls have higher (p<.001) scores (mean=7.04; SD=4.48) than boys (mean=4.78; SD=7.15), and higher prevalence of increased-risk cases. This difference between sexes results mainly from factor “Drive for thinness” (p<.001). Conclusions: A relevant percentage of adolescents revealed attitudes that put them in a spectrum of increased risk for eating disorders (more prevalent in girls). Desire to be thin is the most relevant attitudinal dimension. Health education interventions oriented to set objective and healthy standards of body image and to promote overall self-esteem building among adolescents are strategic to avoid the eventual development of eating disorders.